Early intervention interaction styles questionnaire - Escorcia-Mora, Claudia Tatiana; García-Sánchez, Francisco Alberto; Sánchez-López, María Cristina; Hernández-Pérez, Encarnación (Anales de Psicología / Annals of Psychology, 2015)
Nowadays, Early Childhood Intervention in Spain is taking interest in a family-centred approach. In this context, we present the Styles Questionnaire of Interaction between Parents and Practitioners in Early Intervention –known as SIPPEI (EIPPAT). This is a tool to identify actions, practices and interaction styles conducted by the practitioner to guide families (participative and relational practices). This paper shows the items set of the aforementioned Questionnaire –versions for practitioners and caregivers. Formerly, we detailed the hard work and effort invested to ensure content validity, as we had two focus group –consisting of 15 professionals and 11 parents) and a systematized expert judgment by 11 professionals and 5 mothers. Subsequently, an implementation of the questionnaire was developed by a group of 41 practitioners in order to assess the importance given to the items. The results show that the procedure followed to create the questionnaire accomplishes the main objectives. Thus, we got a questionnaire highly regarded by professionals in this area.